KEPRIBADIAN HARDINESS, DUKUNGAN SOSIAL KELUARGA DAN PROBLEM FOCUSED COPING (PFC) PADA ISTRI PELAUT - Cici Nirmayunita; Weni Endahing Warni; Puri Aquarisnawati (Jurnal Psikologi Poseidon, 2022)
This study determine the relationship between hardiness personality and family social support with problem-focused coping in sailor wives in East Java. Subjects are 70 sailor wives in East Java. The sampling technique used saturated sample. The first hypothesis, that there is a relationship between hardiness personality and problem-focused coping in sailor wives in East Java is accepted with a positive direction. The second minor hypothesis, namely that there is a positive relationship between family social support and the problem Focused Coping in seafarers' wives in East Java, is accepted. Major hypothesis in this research is accepted.